Viscous and Ohmic Heating Effects on MHD Flow of Nanofluid Past a Porous Stretching Sheet with Thermal Radiation and Heat Generation/Absorption: Copper-Alumina Water - Thiagarajan, M.; Kumar, M. Dinesh (Journal of Vibration Testing and System Dynamics, 2026)
The important focus of this work is to numerically examine the viscous dissipation and Ohmic heating effects on hydromagnetic flow of nanofluid over a porous stretching sheet with thermal radiation and heat generation/absorption filled with water-based copper and alumina nanofluids. Heat transfer features are investigated through convective conditions. Consider steady, nonlinear, two-dimensional of an incompressible, viscous and electrically conducting fluid past a porous stretching sheet in the presence variable magnetic field. To obtain meaningful results, we have taken thermal radiation in the heat transfer procedure. Governing nonlinear partial differential equation and they are transformed into an ordinary differential equation by using similarity transformation and the numerical solution is obtained by using Nachtsheim-Swigert shooting iteration scheme together with a fourth order Runge-Kutta integration method. Numerical results are obtained for the velocity and the temperature in the boundary layer region is studied in elaborate. Quantities of engineering interest such as skin friction coefficient and nusselt number are also obtained numerically and are tabulated.